The protective effects of peptides from Chinese baijiu on AAPH-induced oxidative stress in HepG2 cells via Nrf2-mediated signaling pathway - Jiaying Huo; Yuezhang Ming; Huifeng Li; Anjun Li; Jiwen Zhao; Mingquan Huang; Weizheng Sun; Jihong Wu; Jinglin Zhang (Food Science and Human Wellness)
Antioxidant peptides have been widely reported. However, only a few reports have been published examining the antioxidant peptides derived from Chinese baijiu. In this study, 6 novel peptides derived from Chinese baijiu were identified successfully using high-performance liquid chromatography-quadrupole-time-of-flight mass spectrometry (HPLC-QTOF-MS) with a concentration of 0.835–24.540 µg/L. The underlying molecular mechanisms were investigated, and their cytoprotective effects were examined against 2,2’-azobis (2-methylpropanimidamidine) dihydrochloride (AAPH)-induced oxidative stress in HepG2 cells. The results showed that these peptides exerted protective effects by suppressing reactive oxygen species (ROS) generation, preventing malondialdehyde (MDA) formation, and upregulating cellular antioxidant enzyme activities (SOD, CAT, and GSH-Px) in a dose-dependent manner. Further experiments proved that these peptides exerted antioxidant effects via Nrf2/ARE-mediated signaling pathway by promoting Nrf2 nuclear translocation, inhibiting ubiquitination, and enhancing transcription capacity of Nrf2 in HepG2 cells. These findings provide the molecular basis for the effects of antioxidant peptides derived from Chinese baijiu, which is important for a deeper understanding of the relationship between human health and moderate drinking.